2013
DOI: 10.1080/1536710x.2013.784561
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Recovery for Children Disabled in an Earthquake: School Social Work in Dujiangyan, China

Abstract: In the Sichuan earthquake on May 12, 2008, schools were hardest hit. The School Social Work service at the You Ai School of Dujiangyan became a major factor in assisting 140 children, disabled in the disaster, in their psychosocial recovery. This article aims to identify indicators of recovery for children from early primary to junior high. Content analysis is used instead of a lengthy psychological scale, as the latter might not be applicable for young children. Results show that disabled children are capable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
(9 reference statements)
0
7
0
1
Order By: Relevance
“…Just like some previous studies have mentioned (Bolin et al, 2018;Wong, 2013), the review has shown that social workers have relevant roles to play in inclusive education for children with disabilities. Social workers are particularly concerned about addressing the psychological and social issues faced by children with disabilities, which undoubtedly have an impact on their academic performance.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Just like some previous studies have mentioned (Bolin et al, 2018;Wong, 2013), the review has shown that social workers have relevant roles to play in inclusive education for children with disabilities. Social workers are particularly concerned about addressing the psychological and social issues faced by children with disabilities, which undoubtedly have an impact on their academic performance.…”
Section: Discussionmentioning
confidence: 77%
“…Three studies (Agresta, 2004; Hunter et al, 2017; Wong, 2013) further revealed that social workers provide a range of psychoeducation and social services within inclusive education settings. Wong (2013) observed in his study in Hong Kong that social workers have the responsibility to support children with disabilities with their emotional problems to help them thrive in their relationships. According to Wong (2013), children with disabilities may face difficulties building relationships with their non-disabled peers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parknson, Keech dan Emma 2018 (Neumayer dan Pluemper, 2007;Alston, 2018;Drolet et al, 2015;Rowland, 2013;Laksomono, 2008;Wong, 2013;Bauwens dan Naturale, 2017). Sedangkan dilihat dari sudut pandang analisis kebijakan yang digunakan masih secara umum dan belum secara spesifik menggunakan pendekatan sensitive gender (Pancasilawan, 2016;Amalina, 2019;Tan, 2013, Koivisto dan Nohrstedt, 2016Gerber, 2007;Zang, 2018;Tanaka, 2012…”
unclassified
“…After a thorough search of most available databases and other sources, it is evident that most social work studies involving children with disabilities focus either on children with only one disability (e.g., Matz, 2013;Curran, 2010) or on disabled children in general (e.g., Wong, 2013;Diehl, 2003;Middleton, 1998 2) the social worker has specified roles in which to deal with the psychological problems of children with multiple disabilities; and 3) there are differences among children with multiple disabilities in their psychological problems and emotional and behavioral disorders, according to the type of disability.…”
Section: Social Work Studies Of Children With Multiple Disabilities Amentioning
confidence: 99%